2018
DOI: 10.1021/acssuschemeng.7b04092
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Synthesis of Exfoliated Organometal Halide Perovskite Nanocrystals by Ligand-Assisted Ball Milling

Abstract: The scalable synthesis of colloidal organohalide perovskite nanocrystals is essential because of increasing demands for their use in many applications such as photovoltaic and light-emitting devices. However, only subgram quantities of perovskite nanocrystals were produced in the typical precipitation synthesis involving excess amounts of nonsolvent, limiting their high-yield production. In this contribution, ligand-assisted ball milling represents a substantial improvement in the scalability of high quality p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 29 publications
2
52
0
Order By: Relevance
“…Furthermore, the bulk inorganic hybrid perovskite single crystals can be exfoliated into few layers. [70][71][72][73][74][75] Therefore, the thickness of organicinorganic hybrid perovskite can be as thin as 2 nm after exfoliation. Besides the methods mentioned above, melt crystallization techniques such as Czochralski method, Bridgman method and zone-melting method can be also employed to grow large-size industrially important functional crystals.…”
Section: Anti-solvent Vapor-assisted Crystallization (Avc) Methodsmentioning
confidence: 99%
“…Furthermore, the bulk inorganic hybrid perovskite single crystals can be exfoliated into few layers. [70][71][72][73][74][75] Therefore, the thickness of organicinorganic hybrid perovskite can be as thin as 2 nm after exfoliation. Besides the methods mentioned above, melt crystallization techniques such as Czochralski method, Bridgman method and zone-melting method can be also employed to grow large-size industrially important functional crystals.…”
Section: Anti-solvent Vapor-assisted Crystallization (Avc) Methodsmentioning
confidence: 99%
“…39 The structure of EAPbBr 3 has already been reported in the literature and it has a two-dimensional (2D) arrangement. 34,35 The characteristic diffraction peak at $11.3 conrms the 2D arrangement of the EAPbBr 3 NCs. Structural evolutions of the material were studied by TEM analysis and TEM images ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…33 This MOG matrix was utilized as a protecting host matrix to stabilize hybrid bromide perovskite NCs (HBP-NCs) from aerial or chemical degradation. We have also demonstrated that, through encapsulation within a MOG matrix, weakly blue lightemitting, two-dimensional EAPbBr 3 NCs 34,35 (PLQY $ 5%) have achieved an unprecedented ten-fold enhancement in PLQY ($53%) without altering the PL peak position. It is noteworthy that, for the rst time, simultaneous improvement of both PLQY and water stability has been achieved for intense blueemitting hybrid perovskite NCs.…”
Section: Introductionmentioning
confidence: 90%
“…It is a simple method which can lead to higher purity due to the absence of processing additives and solvents. [21][22][23][24][25][26][27][28] Mechanochemical synthesis can be used to synthesize multicomponent compounds simply by mixing the chemical precursors in the appropriate stoichiometry. Impor-www.advopticalmat.de mixed accordingly to the targeted compound's stoichiometry MA 0.8 Cs 0.2 Pb(Br 0.6 Cl 0.4 ) 3 inside a nitrogen-filled glove box and introduced in a 10 mL zirconia ball-mill jar together with zirconia beads.…”
Section: Doi: 101002/adom201901494mentioning
confidence: 99%
“…Solvent‐free “dry” mechanochemical synthesis is an alternative technique to prepare perovskites with virtually any composition. It is a simple method which can lead to higher purity due to the absence of processing additives and solvents . Mechanochemical synthesis can be used to synthesize multicomponent compounds simply by mixing the chemical precursors in the appropriate stoichiometry.…”
mentioning
confidence: 99%